2021
DOI: 10.1002/jwmg.22064
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship and Spatial Patterns of an Urban Population of Texas Horned Lizards

Abstract: Habitat fragmentation has negative consequences on threatened and endangered species by creating isolated populations. The Texas horned lizard (Phrynosoma cornutum) is experiencing population declines and localized extirpations throughout its range and has been classified as a species of greatest conservation need in Oklahoma, USA. Younger age classes have been poorly studied but may be vital to the stability of remaining populations. To address gaps in knowledge concerning subadult (hatchling and juvenile) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
1
1
0
Order By: Relevance
“…Growth rates of THL in our study were greatest during their first 2 years and then slowed thereafter, which is similar to the findings of Vesy et al (2021). The growth rates of THL reported herein were slower than previously reported (Henke and Montemayor 1997), and THL in our study did not obtain the SVL size by their second year as reported by Ballinger (1974).…”
Section: Discussionsupporting
confidence: 92%
“…Growth rates of THL in our study were greatest during their first 2 years and then slowed thereafter, which is similar to the findings of Vesy et al (2021). The growth rates of THL reported herein were slower than previously reported (Henke and Montemayor 1997), and THL in our study did not obtain the SVL size by their second year as reported by Ballinger (1974).…”
Section: Discussionsupporting
confidence: 92%
“…classes are sorely lacking in general across vertebrate taxa (e.g., aves - Cox et al, 2014;Dunn et al, 2017;marine megafauna -Hays et al, 2016;reptiles -Delaney and Warner, 2016;Vesy et al, 2021), and filling these gaps should be of paramount conservation concern (Roznik et al, 2009;Cox et al, 2014). Without an understanding of habitat use and selection by juvenile animals, our perception of a species' habitat requirements becomes framed around knowledge of adult animals.…”
mentioning
confidence: 99%